Overcoming the shadow and achieving individuation through a Hero's journey in Tunku Halim's "A Sister's Tale" - Akam, John Helvy; Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2018)
In Jungian psychology, Individuation is the process of achieving psychological maturation wherein individuals are able to integrate their conscious and unconscious mind to create a balanced psyche. One aspect of the unconscious mind that needs to be integrated with the conscious is the Shadow, a psychological component consisting of all rejected and repressed aspects of one's personality. The process of dealing with the Shadow aspect is analogous to the journey of the Hero archetype, and the goal of this journey is Individuation, whereby one becomes connected to their Self, an archetype that represents wholeness and totality. In Tunku Halim's "A Sister's Tale" (1999), Jessica has been pulled into a Hero's journey because of an unaddressed repressed guilt that ultimately becomes her Shadow. This paper aims to examine Jessica's Heroic journey in attaining her Self through the integration of her unconscious component, the Shadow, with her consciousness. To achieve this objective, the text is analysed through Jungian's concept of the Shadow and Hero archetypes. The findings reveal that Jessica's Shadow had become too dense for a successful integration to occur and therefore, she failed to achieve Individuation.